2018
DOI: 10.1007/s11033-018-4192-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of microsatellite markers for endangered species Stipa pennata (Poaceae) and their usefulness in intraspecific delimitation

Abstract: Stipa pennata (Poaceae), has become a rare and endangered species in Central Europe due habitat loss and fragmentation. This species is characterized by high morphological variability, which has resulted in the description of numerous intraspecific taxa. The aim of present work is to develop microsatellite markers useful in population genetics studies as well as in intraspecific taxonomy of S. pennata s.l. We developed ten microsatellite markers using Illumina high-throughput. Polymorphism at each marker was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…DNA from fresh, young leaves was extracted using E.Z.N.A.® Plant DNA DS Kit (Omega) following manufacturer’s instructions and DNA concentration was measured with Thermo 2000 Nanodrop. Ten pairs of SSR primers (Eurofins, Table 2 ) were selected based on the previous study on a closely related grass species ( Stipa pennata ) [ 65 ] as there is lack of any type of nucleotide sequence information available on the species of our interest. Polymerase Chain Reaction (PCR) was performed in 20 µL reaction mixture containing 50 ng genomic DNA, 0.5 µM of each primer (forward and reverse), 200 µM dNTP (Thermo Scientific™), 2.5 units DreamTaq DNA Polymerase (Thermo Scientific™), 1X PCR buffer (10X buffer with 20 mM MgCl 2 ) and 1 µL Bovine Serum Albumin (BSA, 100 mg·mL –1 stock).…”
Section: Methodsmentioning
confidence: 99%
“…DNA from fresh, young leaves was extracted using E.Z.N.A.® Plant DNA DS Kit (Omega) following manufacturer’s instructions and DNA concentration was measured with Thermo 2000 Nanodrop. Ten pairs of SSR primers (Eurofins, Table 2 ) were selected based on the previous study on a closely related grass species ( Stipa pennata ) [ 65 ] as there is lack of any type of nucleotide sequence information available on the species of our interest. Polymerase Chain Reaction (PCR) was performed in 20 µL reaction mixture containing 50 ng genomic DNA, 0.5 µM of each primer (forward and reverse), 200 µM dNTP (Thermo Scientific™), 2.5 units DreamTaq DNA Polymerase (Thermo Scientific™), 1X PCR buffer (10X buffer with 20 mM MgCl 2 ) and 1 µL Bovine Serum Albumin (BSA, 100 mg·mL –1 stock).…”
Section: Methodsmentioning
confidence: 99%
“…Using transcriptome sequencing, Ren et al [31] developed 21 microsatellite markers of S. breviflora and tested the polymorphism in six related species. Klichowska et al [32] mined 10 microsatellite markers of S. pennata using Illumina high-throughput. Transcriptome analysis has also been used to uncover the adaptive mechanisms of plants subjected to grazing.…”
Section: Introductionmentioning
confidence: 99%
“…breviflora and tested the polymorphism in six related species. Klichowska et al [ 32 ] mined 10 microsatellite markers of S . pennata using Illumina high-throughput.…”
Section: Introductionmentioning
confidence: 99%
“…SSR markers are widely distributed across the genome and they are commonly applied in establishing genetic structure in Stipa . Previously, polymorphic microsatellite primers were reported in populations of S. purpurea (11 113 , 15 114 and 29 115 loci), S. pennata (7 loci 116 ), S. breviflora (21 loci 117 ) and S. glareosa (9 loci 118 ). In the present study, we identified 77,614 perfect SSR markers (Supplementary File 3) and 58 imperfect repeat motifs presented only in a single copy (Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%